When helping hurts : how to alleviate poverty without hurting the poor... and yourself - Corbett, Steve (Moody Publishers, 2012)
Churches and individual Christians typically have faulty assumptions about the causes of poverty, resulting in the use of strategies that do considerable harm to poor people and themselves. When Helping Hurts provides foundational concepts, clearly articulated general principles and relevant applications. The result is an effective and holistic ministry to the poor, not a truncated gospel. A situation is assessed for whether relief, rehabilitation, or development is the best response to a situation. Efforts are characterized by an "asset based" approach rather than a "needs based" approach. Short term mission efforts are addressed and microenterprise development (MED) is explored. --from publisher description.